Anti-crisis purpose of the monetary policy instruments of the Central bank of Russia - V. A. Bredikhina (Вестник Северо-Кавказского федерального университета)
Introduction. The article examines the anti-crisis orientation of the instruments used by the Central Bank of the Russian Federation in order to stabilize the national economy in 2023 and achieve the target inflation rate of 4% in 2024.Goal. The article is devoted to the study of the problems of the functioning of the financial system of the Russian Federation during the period of sanctions pressure from the United States and EU countries.Materials and methods. The study is based on the consideration of theoretical and applied aspects of monetary policy pursued by the Central Bank of the Russian Federation in the context of the economic crisis that began in February 2022. The methodology of the study of the problems of interaction between the Central Bank of the Russian Federation and financial institutions is characterized by an integrated approach to assessing its results, which change under the influence of the unfriendly behavior of these countries in monetary policy and other information sources.Results and discussion. The article proves that the increase in inflation in Russia was caused by the crisis that arose due to the economic sanctions of the EU and the United States applied to our country, as well as an imbalance in the supply and demand of funds in the domestic market of working capital. This state of affairs requires the timely use of effective monetary policy instruments of the Central Bank of Russia. The proposals for the implementation of the monetary policy of the Russian Federation in the situation of deviation of the inflation rate from its target value are presented.Conclusion. The conclusions and generalizations of the study can be used to develop strategies that help offset the negative consequences of the global crisis and return the Russian economy to the basic scenario of its development, taking into account the target inflation rate of 4%. The scientific significance of the article lies in the theoretical understanding of the anti-crisis orientation of the monetary policy instruments pursued by the Central Bank of the Russian Federation in the sanctions environment. The practical significance of the study lies in the fact that its provisions can be used in the process of developing programs for the development of the financial system of the Russian Federation.